Antioxidants in the Treatment of Amyloidosis: a Literature Review - Anconetani, María V.; Llesuy, Susana; Aguirre, María A.; Nucifora, Elsa; Carretero, Marcelina; Posadas Martínez, María L. (Revista del Hospital Italiano de Buenos Aires, 2024)
Introduction: The primary objective of this review is to examine the current scientific evidence regarding the role of antioxidants in relation to amyloidosis. Oxidative stress has been studied in amyloidosis, and a narrative review of articles concerning the use of antioxidants in the treatment of these diseases was conducted. State of the Art: Articles published from 2010 to 2022 are presented, focusing on the use of carvedilol, epigallocatechin gallate (EGCG), resveratrol, and tetracyclines in amyloidosis models and cases. Discussion/Conclusion: Antioxidant therapy for amyloidosis is in its early stages of development, requiring further clinical studies to assess long-term effectiveness and safety. Antioxidants such as carvedilol and EGCG show significant potential in interfering with amyloid fibrils, but additional research is needed to fully comprehend their impact and viability as long-term treatments.